2021
DOI: 10.1111/hepr.13613
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular adenoma, approximately half and predominantly inflammatory subtype, in 38 Japanese patients with several differences in age, gender, and clinical background factors from Western populations

Abstract: Aim: Hepatocellular adenoma (HCA) has a lower prevalence in Japan than in Western countries and HCA subtypes have been reported for only a few Japanese patients. We analyzed HCA subtype data 38 patients from 23 hospitals in Japan in order to examine character and difference between Western countries. Methods: To confirm HCA and to analyze subtypes, we performed immunohistochemical examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In western countries, only ~10% of HCAs are observed in males. A slight male preponderance or a practically equal distribution of male and female patients have been reported in studies from eastern countries with very low OC use 22,113,114 . In these studies, IHCA was the most frequent subtype observed both in the total study population and in the male patients.…”
Section: Hca In Particular Clinicopathological Contextsmentioning
confidence: 67%
See 2 more Smart Citations
“…In western countries, only ~10% of HCAs are observed in males. A slight male preponderance or a practically equal distribution of male and female patients have been reported in studies from eastern countries with very low OC use 22,113,114 . In these studies, IHCA was the most frequent subtype observed both in the total study population and in the male patients.…”
Section: Hca In Particular Clinicopathological Contextsmentioning
confidence: 67%
“…A slight male preponderance or a practically equal distribution of male and female patients have been reported in studies from eastern countries very low OC use. 22,113,114 In these studies, IHCA was the most frequent subtype observed both in the total study population and in the male patients. Overweight and obesity were associated with the IHCA subtype in two of the three studies, 22,113 and the third study 114 mentioned excessive alcohol intake in all IHCA patients but none patients with the other subtypes.…”
Section: H C a I N M A L E Smentioning
confidence: 79%
See 1 more Smart Citation
“…However, epidemiological data from Asia, where the use of OCPs and the incidence of obesity are lower, are unclear. Limited studies from Taiwan, China and Japan showed a male predominance in patients with HCA[ 7 - 11 ]. Further exploration of these epidemiological differences is needed to better understand the pathogenesis of HCA.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Thus, our high proportion of β-HCA or β-IHCA (40%) is in accordance with the literature. I-HCA represents the major subtype in surgical series, 10 more often resected than H-HCA due to the risk of malignant transformation and the potential association with β-catenin mutations. Moreover, I-HCA resected in our study were large tumors, with a mean size of 9.2 cm (5.5-16), all of which were larger than 5 cm.…”
mentioning
confidence: 99%